(untitled) (Journal of Pathology of Nepal, 2022)
Background: Renal tumours are 16th most common malignancies in the world accounting for 2.2% of all new malignancies and 1.8% of all cancer deaths. Histopathological classification of renal tumours along with tumour grade and stage is proven to have prognostic value. Material and Methods: This was a retrospective study conducted in Department of Pathology at B.P. Koirala Memorial Cancer Hospital Bharatpur from January 2017 to December 2019 including cases of partial and radical nephrectomies of patients more than sixteen years of age. Results: Total 78 nephrectomy specimens were received out of which 70 (89.7% consisted of malignant tumour and 8 (10.3%) were benign lesions. Clear cell type renal cell carcinoma was the most common malignant tumour consisting of 57 (81.4%) cases of renal cell carcinoma, followed by papillary type 9(12.9%), Cchromophobe (4.3%) and one case (1.3%) of multiloculated cystic renal neoplasm was noted. Renal cell carcinoma was seen in age range of 26 to 80 years with majority of patients more than 50 years of age, while a small peak (14.3%) was noted in female patients of 31 to 40 years of age. Conclusions: This study found increased incidence of renal cell carcinoma among female patients of 31 to 40 years of age in contrast to studies done in the Western population.